The Effect of the Information Motivation Behavioral Skills (IMB) Model on Fluid Adherence of Hemodialysis Patients - Safruddin Safruddin; Nurul Husnah; Rika Novita; Arya Zahwa Abila Junaedi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Patients undergoing hemodialysis therapy often experience problems with excessive Interdialytic Weight Gain (IDWG) increase. The Information–Motivation–Behavioral Skills (IMB) model has been widely used in health behavior modification, but its application to fluid management of hemodialysis patients is still limited. Therefore, IMB-based interventions are needed to improve fluid adherence. This study aims to determine the influence of the IMB model on fluid adherence (IDWG) of hemodialysis patients. This study uses a quasi-experiment design with a two-group pretest-posttest approach, namely the intervention group and the control group. A total of 70 hemodialysis patients were divided into two groups, each of which was given different treatment. The intervention group received IMB-based education for 4 weeks, including information improvement, personal and social motivation, and behavioral skills. Data were collected from haemodialysis patients who met the inclusion criteria through observation sheets. Interdialytic weight gain (IDWG) was assessed by calculating the difference between post-dialysis and pre-dialysis body weight. Statistical analysis using Wilcoxon and Mann–Whitney tests. There was a significant effect on IDWG in the intervention group with p = 0.000, while the control group showed no significant change (p = 0.165). There was a significant difference between the two groups in IDWG after intervention with p = 0.003. The application of the Information Motivation Behavioral Skills (IMB) Model education has proven to be effective in improving fluid adherence of patients undergoing hemodialysis therapy. The application of the Information Motivation Behavioral Skills (IMB) model education is recommended as part of standard practice in fluid management of hemodialysis patients.